Marsupiais como hospedeiros de manutenção de leptospiras patogênicas no Vale do Rio Paranaíba, estados de Goiás e Minas Gerais, Brasil - Moreia, R. Q.; Ramos, V. N.; Vieira, R. F; Mangueira, R. A. F.; Pires, B. C.; Libonati, H.; Lilenbaum, W.; Lima, A. M. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Small non-flying mammals hold the largest number of species within the Mammalia class in Brazil. Mainly rodents and marsupials, important reservoirs hosts of pathogenic serovars of leptospires, represent this group of animals.